JILBAB PERSPEKTIF QURAISH SHIHAB (STUDI KOMPARASI TAFSIR TULIS DAN LISAN) - Amalia, Ani; Utami, Hilma Azmi; Munawir, Munawir; Fahrur Rozi, Ahmad (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2022)
This study will discuss the comparison between Written and Oral interpretations Of the Quraish shihab's hijab (jilbab) perspective. The Quraish Shihab's interpretation of the verses about the hijab caused a lot of controversy among commentators and scholars. He said that the veil was a must And He Also Said That It Was Not permissible because it cannot be said to be shari'ah without a clear text. In this research, the writer uses the method of over-the-top and long-winded orality and literacy. This feature keeps the listener focused and on the path of the story. It also aims to reveal the differences in the written intbn/ rpretation (Tafsir Al-Misbah) and the oral Quraish shihab. Through this method, the writer assumes that within a boundary there is a difference in meaning between written and oral interpretation. First, in Q.S Al-Ahzab verse 59 his written commentary Quraish Shihab only mentions the word genitalia once, but in his oral interpretation Quraish Shihab mentions the word genitalia repeatedly and ramblingly "aurat must still be covered, genitalia." Second, in Q.S An-Nur Verse 31 of his commentary Quraish shihab he only mentions the word "show" once. While in his oral interpretation, he mentions the word repeatedly or exaggerating. Third, in Q.S Al-A'raf verse 26 the word clothing has a meaning that is repeated, so that the quote contains exaggeration, length and rambling